Regulation of epithelial chloride transport by tyrosine phosphorylation - Loureiro, Cláudia (2016)
In a recent study we reported the regulation of the chloride channel CFTR (Cystic Fibrosis Transmembrane Regulator Condutance) by a novel WNK4/SYK signaling pathway regulating the amount of CFTR at the cell surface. Tyrosine kinase Syk was shown to phosphorylate CFTR and promote its removal from the plasma membrane. In order to study whether Syk may also operate in the regulation of other ion channels or co-transporters, their protein sequences were inspected for the presence of this consensus motif. Among 20 different transport proteins, the Syk motif was identified in the sequence of some further ion transporters.